Furin and TMPRSS2 Resistant Spike Induces Robust Humoral and Cellular Immunity Against SARS-CoV-2 Lethal Infection - Lin, Jhe-Jhih; Tien, Chih-Feng; Kuo, Yi-Ping; Lin, En-Ju; Tsai, Wei-Hsiang; Chen, Ming-Yu; Tsai, Pei-Ju; Su, Yu-Wen; Pathak, Nikhil; Yang, Jinn-Moon; Yu, Chia-Yi; Chuang, Zih-Shiuan; et al. (Frontiers in Immunology, 2022)
An effective COVID-19 vaccine against broad SARS-CoV-2 variants is still an unmet need. In the study, the vesicular stomatitis virus (VSV)-based vector was used to express the SARS-CoV-2 Spike protein to identify better vaccine designs. The replication-competent of the recombinant VSV-spike virus with C-terminal 19 amino acid truncation (S∆19 Rep) was generated. A single dose of S∆19 Rep intranasal vaccination is sufficient to induce protective immunity against SARS-CoV-2 infection in hamsters. All the clones isolated from the S∆19 Rep virus contained R682G mutation located at the Furin cleavage site. An additional S813Y mutation close to the TMPRSS2 cleavage site was identified in some clones. The enzymatic processing of S protein was blocked by these mutations. The vaccination of the R682G-S813Y virus produced a high antibody response against S protein and a robust S protein-specific CD8 T cell response. The vaccinated animals were protected from the lethal SARS-CoV-2 (delta variant) challenge. The S antigen with resistance to enzymatic processes by Furin and TMPRSS2 will provide better immunogenicity for vaccine design.